2023
DOI: 10.3390/ma16103738
|View full text |Cite
|
Sign up to set email alerts
|

The Usability of Sorbents in Restoring Enzymatic Activity in Soils Polluted with Petroleum-Derived Products

Abstract: Due to their ability to adsorb or absorb chemical pollutants, including organic compounds, sorbents are increasingly used in the reclamation of soils subjected to their pressure, which results from their high potential in eliminating xenobiotics. The precise optimization of the reclamation process is required, focused primarily on restoring the condition of the soil. This research are essential for seeking materials sufficiently potent to accelerate the remediation process and for expanding knowledge related t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 123 publications
0
13
0
Order By: Relevance
“…Different results were reported by Gospodarek et al [38], who observed that soil contamination with diesel oil strongly inhibited dehydrogenase and urease activity, with little effect on acid and alkaline phosphatase activity. These results are difficult to dispute, as the degree of biodegradation activity of petroleum-derived substances depends, among other factors, on microbial activity, nutrient availability, oxygen availability, temperature, pH, salinity, as well as the type and degree of pollution and time [36,[115][116][117][118].…”
Section: Soil Biochemical Activitymentioning
confidence: 99%
See 3 more Smart Citations
“…Different results were reported by Gospodarek et al [38], who observed that soil contamination with diesel oil strongly inhibited dehydrogenase and urease activity, with little effect on acid and alkaline phosphatase activity. These results are difficult to dispute, as the degree of biodegradation activity of petroleum-derived substances depends, among other factors, on microbial activity, nutrient availability, oxygen availability, temperature, pH, salinity, as well as the type and degree of pollution and time [36,[115][116][117][118].…”
Section: Soil Biochemical Activitymentioning
confidence: 99%
“…The increased soil pH influenced the improvement of its biological activity, as highlighted by Mahmud and Chong [107]. Higher soil pH is responsible for breaking ionic and hydrogen bonds in the active center of dehydrogenases, an enzyme that indicates the intensity of respiratory metabolism in soil microorganisms [27,36,119]. According to Nannipieri et al [120], Mierzwa-Hersztek et al [121], and Piotrowska-Długosz et al [122], dehydrogenases are enzymes considered as indicators of soil biochemical and microbiological activity.…”
Section: Soil Biochemical Activitymentioning
confidence: 99%
See 2 more Smart Citations
“…The following soil tests were carried out: granulometric composition with laser diffraction using Mastersizer 2000 analyzer (Malvern Instruments Ltd., Malvern, UK), pH using the potentiometric method in 1 mol KCl dm −3 , hydrolytic acidity and the sum of exchangeable base cations with titration, soil sorption capacity, degree of soil saturation with base cations, and organic carbon and total nitrogen contents using a Vario Max Cube CN device (Elementar Analysen systeme GmbH, Langenselbold, Germany). The methodology for the physical and chemical soil tests can be found in Wyszkowska et al [33].…”
Section: Physical and Chemical Soil Testsmentioning
confidence: 99%